2021
DOI: 10.1007/s13595-020-01024-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct analysis in real-time (DART) time-of-flight mass spectrometry (TOFMS) of wood reveals distinct chemical signatures of two species of Afzelia

Abstract: Key message Distinct chemical fingerprints of the wood of Afzelia pachyloba and A. bipindensis demonstrated an effective method for identifying these two commercially important species. Direct analysis in real-time (DART) timeof-flight mass spectrometry (TOFMS) allowed high-throughput examination of chemotypes with vast potential in taxonomic, ecological, and forensic research of wood.• Context Afzelia is a genus of valuable tropical timber trees. Accurate identification of wood is required for the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Kitin et al. [ 42 ] used DART-TOFMS to study two species of Afzelia , Afzelia pachyloba and Afzelia bipindensis . Although the two species are not easily separated using the IAWA standard microscopic wood features, the results using DART-TOFMS reached an accuracy of 78%.…”
Section: Discussionmentioning
confidence: 99%
“…Kitin et al. [ 42 ] used DART-TOFMS to study two species of Afzelia , Afzelia pachyloba and Afzelia bipindensis . Although the two species are not easily separated using the IAWA standard microscopic wood features, the results using DART-TOFMS reached an accuracy of 78%.…”
Section: Discussionmentioning
confidence: 99%
“…In Ravindran et al [20], 10 species of the Meliaceae family were identified based on deep convolutional neural networks, achieving an accuracy of 87% at species the level and an accuracy of 96% at the genus level. Kitin et al [26] used DART-TOFMS to study two species of Afzelia, Afzelia pachyloba and Afzelia bipindensis. Although the two species are not easily separated using the IAWA standard microscopic wood features, the results using DART-FORMS reached an accuracy of 78%.…”
Section: Discussionmentioning
confidence: 99%
“…Deklerck and Price et al (2021) showed that Baillonella toxisperma can be separated from other Sapotaceae species (Autranella congolensis, Tieghemella africana and T. heckelii) via DART TOFMS data and Discriminant Analysis of Principal Components (DAPC) (LOOCV = 96.61%). Kitin et al (2021) utilized DAPC to separate Afzelia bipindensis from A. pachyloba with a LOOCV accuracy of 78%; the low accuracy of the model was linked to the variability of mass spectra within each species group. Finally, Price et al (2021) separated seven species of Pterocarpus including P. erinaceus, P. soyauxii, P. santalinus, P. dalbergioides, P. indicus, P. macrocarpus and P. tinctorius using support vector machine (SVM) and DAPC; LOOCV accuracy of the models was 94% and 95%, respectively, and blind test accuracy was 100% for both models.…”
Section: Studies Using Chemical Methods -Dart Tofmsmentioning
confidence: 99%
“…These studies have shown that wood analysis using DART TOFMS allows for rapid and reliable identification to genus or species level, and, once initial equipment costs are met, analysis is relatively straightforward and cheap (Dormontt et al 2015;Kitin et al 2021). DART TOFMS has been proven to be a clear contender as a means of supporting law enforcement agencies in the US, with leading Customs and Border Protection (CBP) to procure three of the instruments for testing different substances and materials including wood (Clark 2017).…”
Section: Studies Using Chemical Methods -Dart Tofmsmentioning
confidence: 99%